2022
DOI: 10.1001/jamanetworkopen.2022.26236
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of COVID-19 Infection and Messenger RNA Vaccination Among Patients With a History of Kawasaki Disease

Abstract: ImportanceKawasaki disease (KD) symptoms significantly overlap with multisystem inflammatory syndrome in children due to COVID-19. Patients with KD may be at risk for adverse outcomes from exposure to SARS-CoV-2 infection or vaccination.ObjectiveTo describe the outcomes of patients with KD to SARS-CoV-2 infection or vaccination.Design, Setting, and ParticipantsThis case series evaluated 2 cohorts using an existing KD database and reviewed individual electronic medical records for the period spanning January 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Less is known about outcomes of COVID-19 in children with a history of Kawasaki disease. In a study which used electronic medical records obtained from Washington State, in the United States, COVID-19 did not result in higher rates of hospitalization or severe disease in 37 patients with a history of Kawasaki disease ( 7 ). However, this study did not include echocardiographic or laboratory data.…”
Section: Introductionmentioning
confidence: 96%
“…Less is known about outcomes of COVID-19 in children with a history of Kawasaki disease. In a study which used electronic medical records obtained from Washington State, in the United States, COVID-19 did not result in higher rates of hospitalization or severe disease in 37 patients with a history of Kawasaki disease ( 7 ). However, this study did not include echocardiographic or laboratory data.…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, a report from Seattle noted that patients with a prior history of KD did not have adverse outcomes when either infected with SARS-CoV-2 or vaccinated with mRNA COVID-19 vaccines. 82 …”
Section: Introductionmentioning
confidence: 99%
“…However, in a large cohort study on KD patients who were administered with two mRNA vaccines, BNT162b2 or mRNA-1273, it has been shown that mRNA vaccines may be safe and tolerable, and also, infection with COVID-19 might not be severe for individuals with a history of KD. 24 Still, limited information exists, and immune responses of KD patients against COVID-19 immunization are unclear.…”
Section: Introductionmentioning
confidence: 99%